An alternative explanation of leontief's paradox (1994)
Leontief's paradox has had a profound impact on theoretical andempirical research in international economics. Ever since the paradoxwas produced, efforts have been made to refute it., confirm it orsimply explain it, and the debate still continues. Based on the Sraffamodel, this article proposes an alternative explanation to thoseapplying orthodox arguments, showing the theoretical plausibility ofthe paradox.